NEW ENVIROMENTAL PARADIGMA (NEP) DALAM MENGUKUR KESIAPAN BERPERILAKU RAMAH LINGKUNGAN PADA SEKOLAH ADIWIYATA DI PONOROGO - Patriana, Wahyu Ria (ASANKA : Journal of Social Science and Education, 2020)
The purpose of this study was to determine the readiness of sustainable behavior towards Environmental students of SMA Negeri 3 Ponorogo as a national adiwiyata as a form of EfSD. This research was designed as a quantitative descriptive study. The study was conducted at SMA Negeri 3 Ponorogo. The subjects were students are in SMA N 3 Ponorogo. The data collection technique that researchers used in this study was a questionnaire. The instrument in this study was the NEP questionnaire. Data analysis in this study was carried out using qualitative and quantitative analysis techniques. The results of the questionnaire are known that students' readiness of sustainable behavior on each indicator has shown good results. The limits to growth component shows the results of an understanding of the limitations of the earth in providing natural resources that students have mastered. The anti-anthropocentrism component shows that no student has a high ego towards the environment. The balance of nature component shows students have no potential to damage nature in the future. In the anti-exemptionalism component students can already be responsible for the environment. The eco-crisis component shows that students can already understand about the environmental damage mostly caused by humans.